Neurobrucellosis: A Case Report from Himachal Pradesh, India, and Review of the Literature - Sujeet Raina (Case Reports in Infectious Diseases, 2016)
Human brucellosis is a multisystem disease that commonly presents as a febrile illness along with variable spectrum of clinical manifestations. Neurological complications include encephalitis, meningoencephalitis, radiculitis, myelitis, peripheral and cranial neuropathies, subarachnoid hemorrhage, and psychiatric manifestations. We report a case diagnosed as neurobrucellosis who presented with fever and bilateral upper motor neuron symptoms and signs along with bilateral sensorineural deafness. Diagnosis was confirmed by Rose Bengal Test (RBT) and standard tube agglutination test (SAT).